2021
DOI: 10.1177/00405175211028803
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of sliver blending and evaluation of blending irregularity

Abstract: The quality of blended yarn depends on the uniformity of the blending of the multi-component fibers in the yarn, and sliver blending is a process necessary for mixing fibers. The movement of fibers directly affects the distribution and mixing of fibers in the sliver. In this paper, the sliver blending process was simulated, and a method for the evaluation of sliver blending irregularity was proposed. The effects of passages of drawing and blending ratio on the sliver mixing uniformity were studied and verified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…According to the division method of blended sliver in the previous study, 15,16 the center of gravity of the yarn/sliver cross section was taken as the center, and the maximum radius was the radius of the yarn/sliver, then the cross section was divided into 60 fan-rings consisting of 10 fans and six rings, as shown in Figure 11. The center of gravity coordinate is where, sumX is the sum of X coordinates of the pixels in the image of the target image, and sumY is the sum of Y coordinates.…”
Section: Image Processing Methods For Blending Irregularitymentioning
confidence: 99%
See 2 more Smart Citations
“…According to the division method of blended sliver in the previous study, 15,16 the center of gravity of the yarn/sliver cross section was taken as the center, and the maximum radius was the radius of the yarn/sliver, then the cross section was divided into 60 fan-rings consisting of 10 fans and six rings, as shown in Figure 11. The center of gravity coordinate is where, sumX is the sum of X coordinates of the pixels in the image of the target image, and sumY is the sum of Y coordinates.…”
Section: Image Processing Methods For Blending Irregularitymentioning
confidence: 99%
“…According to the test method of blending irregularity proposed in our previous study, 15,16 the yarn/sliver was divided as shown in Figure 3, and the blending ratio of each component fiber in each fan-ring was measured respectively. As mentioned in previous studies, 15,16 the blending irregularity of smallest component was used to express the blending irregularity of the blended yarn. Substituting the ratio of blending within each fan-ring of the smallest components into formula (1), the blending irregularity C can be calculated.…”
Section: Blending Irregularity Calculationmentioning
confidence: 99%
See 1 more Smart Citation